PROPOSALS TO IMPROVE THE RELIABILITY MODELING IN THE CASES OF TRUNCATED TESTS - Jan-Cristian GRIGORE; Alexandru BOROIU; Andrei-Alexandru BOROIU (Fiabilitate şi Durabilitate)
For modeling the reliability, there are used specifically designed computing programs, two situations being possible: complete tests and incomplete tests. However, it is found that in the cases of incomplete tests it is not made distinguish between the censored type testing (which ends when a preset number of products of considered batch failed) and the truncated type testing (which ends at a predetermined time moment). In the case of the incomplete type testing, there is not taken into consideration the time interval between the moment of the last failure and the moment of the end of the experiment (the case of truncated type testing). Therefore, based on the realized study, there is proposed a computing algorithm for modeling the reliability through the usual mathematical laws (Weibull, exponential, normal) when trying truncated type. The results obtained confirm the usefulness of theoretical and practical computational algorithms proposed